Stomatal Characteristics in Three Groups of Mangrove Plants: Major, Minor, and Associate - Febrina Artauli Siahaan; Dewi Lestari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2023)
Three types of mangroves inhabit different environmental gradients and zones within the mangrove ecosystem. These three mangrove types exhibit distinct adaptation strategies. Stomata, as a crucial organ of the plant system, play a significant role in the adaptability of plants. Understanding stomata is essential for comprehending the physiological conditions and responses of plants to environmental conditions. This research aimed to study the stomatal characteristics of three different mangrove types and gain a deeper understanding of their potential adaptive strategies. This research was conducted at the Mangrove Botanical Garden Gunung Anyar, Surabaya, in November 2022. We selected two representative mangrove species from the major, associate, and minor types. Stomata of each mangrove species were observed to identify the stomatal type, density, and size using an Olympus microscope at 100 xs and 400 x magnifications. The results showed there were variations in stomatal type, density, and stomatal length and width among studied mangrove types. Major mangrove species exhibited the lowest stomatal density and the largest size of stomata compared to minor and associated mangroves. The diversity of stomatal traits among major, associate, and minor mangrove types underscores their adaptations and ecological strategies.